Study of Local Plant as a Functional Food to Increase Breast Milk Supply - Rike Puspitasari; Rahajeng Siti Nur Rahmawati; Arika Indah Setyarini (STIKes Patria Husada Blitar, 2022)
Exclusive breastfeeding for 6 months is one of the global strategies to improve infant growth, development, health and survival. One of the efforts that support the success of breastfeeding is by providing additional food in the form of local plants as functional food ingredients to increase breast milk supply and avoid less than optimal milk production. This research was conducted to explain the content of local plants as functional food ingredients that can help increasing breast milk supply. This literature study research used secondary data from the Google Scholar, Pubmed, Science Direct database with the last 5 years published, and then the journals obtained are identified according to the inclusion and exclusion criteria set by the researcher. The results of a review of 12 journals stated that local plants Moringa leaf, katuk leaf, mung beans, and soybeans as functional food ingredients that can increase breast milk supply because the four plants contain laktagogum effects that can stimulate, maintain and increase breast milk. Local plants Moringa leaf, katuk leaf, mung beans and soybeans as functional food ingredients to increase breast milk supply because they have a laktagogum effect which are consumed in varying doses and ways of consumption, but have the same efficacy, namely increasing the rate of secretion and production of breast milk.